Combined Anterior Cruciate Ligament and Posterolateral Reconstruction of the Knee Using Allograft Tissue in Chronic Knee Injuries - Fanelli, Gregory C.; Fanelli, David G.; Edson, Craig J.; Fanelli, Matthew G. (The Journal of Knee Surgery, 2014)
Combined anterior cruciate ligament (ACL) and posterolateral injury of the knee can result in significant functional instability for the affected individual. Both components of the instability must be treated to maximize the probability of success for the surgical procedure. Higher failure rates of the ACL reconstruction have been reported when the posterolateral instability has been left untreated. The purpose of this article is to describe our surgical technique, and present the results of 34 chronic combined ACL posterolateral reconstructions in 34 knees using allograft tissue, and evaluating these patient outcomes with KT 1000 knee ligament arthrometer, Lysholm, Tegner, and Hospital for Special Surgery knee ligament rating scales. In addition, observations regarding patient demographics with combined ACL posterolateral instability, postoperative range of motion loss, postinjury degenerative joint disease, infection rate, return to function, and the use of radiated and nonirradiated allograft tissues will be presented.
Keywords: anterior cruciate ligament; posterolateral instability; combined ACL posterolateral instability; allograft; mechanical graft tensioning